2007
DOI: 10.1124/dmd.106.013508
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Acute Moderate Hypoxia Are Associated with a Down-Regulation of CYP1A1, 1A2, 2B4, 2C5, and 2C16 and Up-Regulation of CYP3A6 and P-glycoprotein in Liver

Abstract: ABSTRACT:In humans, indirect evidence suggests that hypoxia reduces the rate of biotransformation of drugs cleared by cytochrome P450 (P450) subfamilies CYP1A, 2B, and 2C. The aim of this study was to assess whether acute moderate hypoxia modulates the expression of CYP2B4, 2C5, and 2C16 in vivo, and to determine whether the changes in hepatic P450 are conveyed by serum mediators. Moreover, because hypoxia increases the expression of P-glycoprotein in vitro, we examined whether in vivo acute moderate hypoxia m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 37 publications
(57 reference statements)
3
47
0
Order By: Relevance
“…Elsewhere, hypoxia was also shown to decrease CYP1A-mediated ethoxyresorufin-O-deethylase (EROD) activity in zebrafish embryos (Fleming and Di Giulio, 2011) and cyp1a mRNA levels in Atlantic cod liver (Olsvik et al, 2006). Mammalian in vivo studies using rabbit, and rodent in vitro hepatocyte studies also showed decreases in cyp1a and cyp1a2 mRNA and protein expression by hypoxia, whose effects on CYP1As are mediated through HIF-1α, cellular cytokines and reactive oxygen species (ROS) (Fradette et al, 2007;Fradette and Du Souich, 2004). These studies are direct opposite of the effects of hypercapnia observed in the present study showing persistent increase of cyp1a mRNA in all sampling days.…”
Section: The Combined Effects Of Hypercapnia and Pfosmentioning
confidence: 99%
“…Elsewhere, hypoxia was also shown to decrease CYP1A-mediated ethoxyresorufin-O-deethylase (EROD) activity in zebrafish embryos (Fleming and Di Giulio, 2011) and cyp1a mRNA levels in Atlantic cod liver (Olsvik et al, 2006). Mammalian in vivo studies using rabbit, and rodent in vitro hepatocyte studies also showed decreases in cyp1a and cyp1a2 mRNA and protein expression by hypoxia, whose effects on CYP1As are mediated through HIF-1α, cellular cytokines and reactive oxygen species (ROS) (Fradette et al, 2007;Fradette and Du Souich, 2004). These studies are direct opposite of the effects of hypercapnia observed in the present study showing persistent increase of cyp1a mRNA in all sampling days.…”
Section: The Combined Effects Of Hypercapnia and Pfosmentioning
confidence: 99%
“…Elsewhere, exposure to hypoxia (dissolved oxygen, DO: 1.7 mg/L for 2 to 4 weeks) produced significant decreases in hepatic cyp1a mRNA and protein levels (du Souich and Fradette 2011;Rahman and Thomas 2012). Some studies have suggested post-transcriptional inhibition of CYP1A activity (Fradette et al 2007). It should be acknowledged that gene expression analysis may not directly be translated into enzyme activity.…”
Section: Biotransformation Responsesmentioning
confidence: 99%
“…Cells adapt to reduction in oxygen levels by shifting energy production from mitochondrial fatty acid β-oxidation to glycolysis during periods of cellular hypoxia (Liu et al 2014). Elsewhere, in vivo mammalian studies using rabbit, and rodent in vitro hepatocyte studies reported decreases in cyp1a and cyp1a2 mRNA and protein expression by hypoxia, whose effects are mediated through HIF-1α, cellular cytokines and ROS (Fradette et al 2007;Fradette and du Souich 2004). While these studies may show some discrepancies with our findings, there are direct relevance of the effects of hypoxia observed in the present study showing persistent increase of cyp1a, cyp3a and pxr mRNA.…”
Section: Biotransformation Responsesmentioning
confidence: 99%
“…In these hypoxic conditions, it has been recognized that accumulated HIF-1α increases a wide variety of genes including vascular endothelial growth factor (VEGF), heme oxygenase-1 (HO-1), erythropoietin (EPO) and cytochrome p450 (CYP) 3A6 to ensure adaptation to low-oxygen tension (Levy et al, 1995;Lee et al, 1997). On the other hand, the expression of CYP1A2, 2B and 2C are decreased by the activation of HIF-1α (Olsvik et al, 2006;Fradette et al, 2007). Further, it has been reported that both hypoxia and hypoxia mimetics increase ROS generation and dysregulate adipocytokines, and these conditions lead to and/or promote metabolic disorders (Schuster et al, 1989;Hosogai et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%